2017
DOI: 10.3389/fcimb.2017.00149
|View full text |Cite
|
Sign up to set email alerts
|

The Phytochemical Bergenin Enhances T Helper 1 Responses and Anti-Mycobacterial Immunity by Activating the MAP Kinase Pathway in Macrophages

Abstract: Tuberculosis (TB) remains one of the greatest health concerns worldwide, which has hindered socioeconomic development in certain parts of the world for many centuries. Although current TB therapy, "Directly Observed Treatment Short-course," is effective, it is associated with unwanted side effects and the risk for the generation of drug-resistant organisms. The majority of infected individuals successfully confine the mycobacterial organisms and remain asymptotic unless immune responses are perturbed. Thus, ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 40 publications
0
28
0
1
Order By: Relevance
“…While the present study demonstrated that bergenin plays an anti-inflammatory role via the modulation of MAPK and NF-κB signaling pathways in a mouse model of LPS-induced mastitis [ 45 ]. In addition, the previous study shows that bergenin induces Th1 immune responses and potently inhibits bacillary growth in a murine model of Mycobacterium tuberculosis infection by activating the MAP kinase and ERK pathways [ 46 ]. Therefore, we speculate that the mechanism of the immunomodulatory action bergenin may be though the NF-κB and MAPK pathways.…”
Section: Discussionmentioning
confidence: 99%
“…While the present study demonstrated that bergenin plays an anti-inflammatory role via the modulation of MAPK and NF-κB signaling pathways in a mouse model of LPS-induced mastitis [ 45 ]. In addition, the previous study shows that bergenin induces Th1 immune responses and potently inhibits bacillary growth in a murine model of Mycobacterium tuberculosis infection by activating the MAP kinase and ERK pathways [ 46 ]. Therefore, we speculate that the mechanism of the immunomodulatory action bergenin may be though the NF-κB and MAPK pathways.…”
Section: Discussionmentioning
confidence: 99%
“…This compound activates various signaling pathways, such as the ERK1/2, MAP kinase, and SAPK/JNK pathways, and also induces TNF-α, nitric oxide (NO), and IL-12 production in infected murine macrophages. Bergenin is a hydrolysable tannin derivative and exhibits anti-hepatotoxic, anti-ulcerogenic, anti-HIV, anti-arrhythmic, anti-malarial, anti-inflammatory, neuroprotective, and immunomodulatory effects (Dwivedi et al 2017 ). Bergenin effectively protects against DNA damage, and it has been suggested that its hydroxyl radical scavenging activity is critical for this DNA damage protection (Veerapur et al 2009 ).…”
Section: Naturally Occurring Radioprotectorsmentioning
confidence: 99%
“…Study also showed induction of Th1 and Th17 host-mediated host-protective immune response potent enough to inhibit mycobacterial growth in murine model of M. tb infection. Molecular mechanistic study confirms that bergenin targets the MAP kinase pathway to alter host immune responses (27).…”
mentioning
confidence: 82%
“…Earlier reports from our group highlighted potent immunomodulatory properties of bergenin. In the same report we presented effective reduction of mycobacterial burden in addition to the induction of protective host immune responses (27). We hypothesized that bergenin could be used in adjunct therapy with anti-tuberculosis therapy (ATT) reducing major risks and adverse effects associated with ATT.…”
Section: Co-treatment With Bergenin and Isoniazid Enhances Host Protementioning
confidence: 99%
See 1 more Smart Citation